Novel Highly Luminescent Amine-Functionalized Bridged Silsesquioxanes - Pereira, Rui F. P.; Nunes, Sílvia C.; Toquer, Guillaume; Cardoso, Marita A.; Valente, Artur J. M.; Ferro, Marta C.; Silva, Maria M.; Carlos, Luís D.; Ferreira, Rute A. S.; de Zea Bermudez, Verónica (Frontiers in Chemistry, 2018)
Amine-functionalized bridged silsesquioxanes were synthesized from bis[(3-trimethoxysilyl)propyl] amine via a solvent-mediated route. BS-1 and BS-2 were obtained with neutral pH with sub- and stoichiometric amounts of water, respectively, and high tetrahydrofuran content. BS-3 was prepared with hyperstoichiometric water concentration, high tetrahydrofuran content and hydrochloric acid. BS-4 was synthesized with hyperstoichiometric water concentration, high ethanol content and sodium hydroxide. BS-1 and BS-2 were produced as transparent films, whereas BS-3 and BS-4 formed white powders. Face-to-face stacking of flat or folded lamellae yielded quasi-hydrophobic platelets with emission quantum yields of 0.05±0.01 (BS-1 and BS-2) or superhydrophilic onion-like nanoparticles with exciting emission quantum yields of 0.38±0.03 (BS-3) and 0.33±0.04 (BS-4), respectively. The latter two values are the largest ever reported for amine-functionalized siloxane-based hybrids lacking aromatic groups. Fast Grotthus proton hopping between =NH2+/=NH groups (BS-3) and =N-/=NH groups (BS-4), promoted by H+ and OH- ions, respectively, and aided by short amine-amine contacts provided by the onion-like morphology, account for this unique optical behavior.